114k views
11 votes
Hi. I need help with this question (see image). Please show workings.​

Hi. I need help with this question (see image). Please show workings.​-example-1
User Karishma
by
4.4k points

1 Answer

11 votes

Answer:


(dy)/(dx) = 8(2x + 3)³

Explanation:

Differentiate using the chain rule

Given

y = f(g(x)) , then


(dy)/(dx) = f'(g(x)) × g'(x)

Here

f(x) =
(2x+3)^(4) ⇒ f'(x) = 4(2x + 3)³

g(x) = 2x + 3 ⇒ g'(x) = 2

Thus


(dy)/(dx) = 4(2x + 3)³ × 2

= 8(2x + 3)³

User Mephane
by
5.5k points